2015
DOI: 10.1364/ao.54.000299
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and theoretical analysis on the absorption properties of metasurface-based terahertz absorbers with different thicknesses

Abstract: In this paper, we numerically and theoretically discuss the novel absorption properties of a conventional metasurface-based terahertz (THz) electromagnetic (EM) absorber with different dielectric thicknesses. Two absorption modes are presented in the considered frequency band due to the increased dielectric thickness, and both modes can achieve near-unity absorptions when the dielectric layers reach additional nλ(d)/2 (n=1, 2) thicknesses, where λ(d) is the operating wavelength at the peak absorption in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Some research groups have reported the related works about the higher-order modes in the THz region. For example, Wu et al discussed the absorption behaviors of a THz MA under different dielectric thicknesses and found two absorption modes in the process [17]. Wang et al presented a dual-band THz MA made by a metallic strip, and the dual-band absorption was due to the excitation of the fundamental resonance and high-order mode [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have reported the related works about the higher-order modes in the THz region. For example, Wu et al discussed the absorption behaviors of a THz MA under different dielectric thicknesses and found two absorption modes in the process [17]. Wang et al presented a dual-band THz MA made by a metallic strip, and the dual-band absorption was due to the excitation of the fundamental resonance and high-order mode [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since then the MAs have been designed to exhibit different characteristics such as single-band [10,11], dual-band [12,13], multiband absorption [14][15][16][17] and broadband absorption [18][19][20][21]. Till now, most of the reported MAs are based on planar resonators (2D structure) [11,[22][23][24]. However, the absorbing performance of the planar design will deteriorate significantly under oblique incidences with large incident angles.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials with fractal elements contain structure of repeating self‐similar geometry and their resonant characteristics can be controlled by the fractal levels . Metamaterials with meta‐elements consists of resonators whose dimensions and periodicity are small compared to the operating wavelength . There are also metamaterials with hybrid elements which combine different resonant elements in a unit cell to achieve the desired electromagnetic responses .…”
Section: Introductionmentioning
confidence: 99%